Numerical and experimental studies on extrudate swell of branched polyethylene through axisymmetric and planar dies - Ganvir, Vivek; Gautham, Basavarsu P.; Thaokar, Rochish; Lele, Ashish K.; Pol, Harshwardhan (Journal of Polymer Engineering, 2011)
Extrudate swell is simulated using an Arbitrary Lagrangian Eulerian (ALE) technique based finite element formulation and the same has been validated by comparing the results with reported numerical and experimental studies. In the present work we compare our ALE simulations with our own experimental data on the extrudate swell of commercial grade low density polyethylene (LDPE) resin. The resins were characterized for their rheological behavior in both shear and uniaxial extension. The polymers were extruded from a capillary under isothermal conditions and the extrudates were observed on-line using a video camera. ALE simulations were performed using molecular constitutive model like eXtended Pom-Pom (XPP) for branched (LDPE). The simulated extrudate swell was a good match with the experimental data. It was found that the swell values of LPDE through planar die are higher than the axisymmetric die.
Keywords: ALE-FEM; extrudate swell; polymer flow simulations; XPP